Abram P.T. Elder papers - Elder, Abram P. T. (Abram Peter Turner); Grosvenor, Charles Henry, 1833-1917.; National Biographical Society (Washington, D.C.)
Correspondence, biographical files, business records of the National Biographical Society, illustrated materials, photographs, and other papers pertaining primarily to Elder's creation and publication of biographical directories for the society. Includes research and publication materials for Charles Henry Grosvenor's Book of the Presidents, with Biographical Sketches (1902) and other biographical directories. Also includes materials relating to an exhibit promoting sales of a directory at the Panama-Pacific International Exposition San Francisco, Calif. (1915), and papers pertaining to the Elder's home in Middletown, R.I.
Biographical files contain correspondence, biographical entries, clippings, printed matter, and photographs regarding prominent local, state, and national politicians, capitalists, and philanthropists. Individuals represented include Charles F. Chickering, W.W. Corcoran, Moody Currier, H.A. Du Pont, Mary Baker Eddy, Isaac E. Emerson, Charles W. Fairbanks, Marshall Field, Julius Fleischmann, Ulysses S. Grant II, Solomon R. Guggenheim, William Guggenheim, Edward Everett Hale, Marcus Alonzo Hanna, David N. Hershey, Christian Heurich, Henry Edwards Huntington, Charles Kellogg, Henry Miles Knowles, Daniel Scott Lamont, Craige Lippincott, Nicholas Longworth, Cyrus Hall McCormick, Darius O. Mills, J. Pierpont Morgan, Levi P. Morton, Gottlieb Muhlhauser, Francis G. Newlands, George Mortimer Pullman, and Matthew Stanley Quay.
Biographer and publisher. Died circa 1930.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Chickering, Charles F., -- 1827-1891.; Corcoran, W. W. -- 1798-1888.; Currier, Moody, -- 1806-1898.; Du Pont, H. A. -- 1838-1926.; Eddy, Mary Baker, -- 1821-1910.; Emerson, Isaac E. -- 1859-1931.; Fairbanks, Charles W. -- 1852-1918.; Field, Marshall, -- 1834-1906.; Fleischmann, Julius, -- 1872-1925.; Grant, Ulysses S., -- 1852-1929.; Guggenheim, Solomon R. -- 1861-1949.; Guggenheim, William, -- 1868-1941.; Hale, Edward Everett, -- 1822-1909.; Hanna, Marcus Alonzo, -- 1837-1904.; Hershey, David N., -- 1818-; Heurich, Christian, -- 1842-1945.; Huntington, Henry Edwards, -- 1850-1927.; Kellogg, Charles, -- 1825-1892.; Knowles, Henry Miles, -- 1850-1903.; Lamont, Daniel Scott, -- 1851-1905.; Lippincott, Craige, -- 1846-1911.; Longworth, Nicholas, -- 1869-1931.; McCormick, Cyrus Hall, -- 1809-1884.; Mills, Darius O. -- 1825-1910.; Morgan, J. Pierpont -- 1837-1913.; Morton, Levi P. -- 1824-1920.; Muhlhauser, Gottlieb, -- 1836-; Newlands, Francis G. -- 1848-1917.; Pullman, George Mortimer, -- 1831-1897.; Quay, Matthew Stanley, -- 1833-1904.; Capitalists and financiers -- Biography; Directories; Exhibitions -- California -- San Francisco; Philanthropists -- United States -- Biography; Politicians -- United States -- Biography; Presidents -- United States -- Biography; Publishers and publishing -- United States; Middletown (R.I.) -- History; Biographers; Publishers